Spatiotemporal characteristics of the apparent optical spectrum in the coastal waters of Leizhou Peninsula and their comparative analysis - Li, Yongze; Chai, Xia; Guo, Fengcheng; Sun, Xiong; Cheng, Zhaohui; Fu, Dongyang; Liu, Dazhao (Frontiers in Marine Science, 2025)
IntroductionThe coastal waters of the Leizhou Peninsula, as an important ecological transition zone in the northern South China Sea, face water quality issues that urgently require effective monitoring methods.MethodsBased on data from 188 stations across four seasons from 2020-2024, this study innovatively proposes a quantile statistical classification method based on mean and standard deviation, and compares results with typical bays at similar latitudes globally.ResultsThe research classifies regional water spectral types into four categories: Type I (17.22%) with high reflection narrow peaks at 570 nm; Type II (35.10%) featuring broad peaks at 540-560 nm; Type III (27.81%) showing gentle distribution across 500-570 nm; and Type IV (19.87%) with decreasing reflectance as wavelength increases, peaking around 500 nm.DiscussionResults indicate this region is dominated by mixed turbid waters (Types II and III accounting for 62.91%), providing scientific basis for water quality monitoring, aquaculture planning, algal bloom identification, and marine functional zoning, thus promoting regional marine ecological protection and sustainable resource utilization.